Transition metal single atom embedded GaN monolayer surface for efficient and selective CO2 electroreduction. Issue 45 (9th November 2022) - Umer, Muhammad; Umer, Sohaib; Anand, Rohit; Mun, Jinhong; Zafari, Mohammad; Lee, Geunsik; Kim, Kwang S.
Abstract : A descriptor-based screening approach is adopted to identify stable, efficient and highly selective CO2 RR electrocatalysts. DFT based mechanistic analysis highlighted the potential reduction route towards different C1 products. Abstract : Single-atom catalysts (SACs) have attracted attention for electrochemical conversion of CO2 into valuable products using renewable electricity. Herein, by means of density functional theory (DFT) computations, we report a descriptor-based design principle to investigate the potential of 3d/4d and 5d transition metal (TM) single atoms (SAs) embedded gallium nitride (GaN) monolayers as electrocatalysts for the CO2 reduction reaction (CO2 RR). We show that both initial CO2 adsorption and activation are hugely influenced by an intricate interplay between the local coordination environment, surface charge density and electronic structure properties of catalysts. Based on this analysis, we readily identified 15 TM-SACs which are capable of activating an inert CO2 molecule to form a carbon dioxide radical anion (CO2 ˙ – ). Our mechanistic analysis and descriptor-based screening approach predicted Mn/Rh/Os/Ir-SAC to be one of the most promising CO2 RR electrocatalysts. Remarkably, the proposed lowest free energy pathway analysis indicated that the Rh-SAC has the best activity towards formation of HCOOH with a limiting potential ( U L ) of −0.42 V, while the Ir-SAC exhibits a better catalytic activity for CH4 production with a U L of −0.48 V and a selectivity of 97% against the competing HER process. Our findings provide a deep insight into designing highly selective and efficient CO2 RR electrocatalysts.